STRATEGI BERSAING DALAM MENINGKATKAN MINAT BELI PRODUK PLASTIK MELALUI PROMOSI, HARGA, LOKASI DAN KUALITAS PELAYANAN (Survei pada Pelanggan Pandawa Sumber Plastik, PD. Berkah dan PD. Utama) - Barin Barlian; Lucy Dian Rosalin (Exchall: Economic Challenge, 2022)
The purpose of this study was to determine and analyze the effect of promotion, price, location and service quality on customer buying interest either partially or simultaneously on Pandawa Sumber Plastik, PD. Berkah and PD. Utama. The object of study was Pandawa Sumber Plastik, PD. Berkah and PD. Utama customers. The research method used is path analysis. Data collection was obtained through observation, questionnaires and literature study. The population in this study was 226 customers. The conclusion obtained from this research is that the variable promotion, price, location and service quality have a significant influence on the purchase interest of Pandawa Sumber Plastik, PD. Berkah and PD. Utama customers.